2017
DOI: 10.3390/molecules22040604
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Antifungal Studies of Zinc-Doped Hydroxyapatite Coatings

Abstract: The present study is focused on the synthesis, characterization and antifungal evaluation of zinc-doped hydroxyapatite (Zn:HAp) coatings. The Zn:HAp coatings were deposited on a pure Si (Zn:HAp_Si) and Ti (Zn:HAp_Ti) substrate by a sol-gel dip coating method using a zinc-doped hydroxyapatite nanogel. The nature of the crystal phase was determined by X-ray diffraction (XRD). The crystalline phase of the prepared Zn:HAp composite was assigned to hexagonal hydroxyapatite in the P63/m space group. The colloidal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
3
39
1
1
Order By: Relevance
“…The value of the average electrophoretic mobility was −0.00034 cm 2 V −1 s −1 ( Figure 2C). The value obtained for the ζ-potential in the ZnHAp gel was much higher than which has been reported so far [19,31]. This difference may be due to increasing the zinc concentration, and, on the other hand, to the synthesis parameters.…”
Section: Characterization Of Suspensioncontrasting
confidence: 58%
“…The value of the average electrophoretic mobility was −0.00034 cm 2 V −1 s −1 ( Figure 2C). The value obtained for the ζ-potential in the ZnHAp gel was much higher than which has been reported so far [19,31]. This difference may be due to increasing the zinc concentration, and, on the other hand, to the synthesis parameters.…”
Section: Characterization Of Suspensioncontrasting
confidence: 58%
“…A Duncan’s test confirmed that the influence of nano-ZnO on antimicrobial properties of (K) PE films ( p < 0.001) or PE films covered with MHPC ( p < 0.001) was significant. It was shown [ 21 ] that zinc is effective in inhibiting the growth of C . albicans .…”
Section: Resultsmentioning
confidence: 99%
“…The coating process was carried out at a speed of 2000 rpm by centrifugation for 60 s. Next, the pure Ti disks coated with a composite layers (Ag:HAp-S1 and Ag:HAp-S2 ) were dried for 60 min at 100 • C. Spin-coating and dried procedures were repeated 3 times. Finally, the Ag:HAp-S1 and Ag:HAp-S2 composite layers were thermally treated for 12 h at 300 • C (with heating rate of 1 • C/min) in order to obtain films with a crystalline structure and to remove the solvents [58]. On the other hand, the resulted sol-gel solutions, S1 (mixture stirred a week at 40 • C) and S2 (mixture stirred a week at 80 • C) used to prepare the Ag:HAp-S1 and Ag:HAp-S2 composite layers by spin-coating technique were analyzed for the first time by ultrasonic measurements in order to highlight the stability of these solutions.…”
Section: Layers Of Silver Doped Hydroxyapatite Preparationmentioning
confidence: 99%